To create multifunctional riverscapes : the example of Älvkarleby in the Nedre Dalälven River, Sweden - Ye, Xuan (SLU/Dept. of Urban and Rural Development, 2022)
The natural environment and ecological services of rivers and the needs and expansion of human activities using rivers causes conflicting interests. Human survival is inseparable from the dependence on the natural environment, but at the same time, the continuous demand for natural resources has also caused an irreversible impact. Hydropower is regarded as sustainable and clean energy and is being developed and applied in increasing river basins, while it has also caused damage and pressure on the ecological environment of the rivers. The Nedre Dalälven river has long been considered as one of the important areas for wild salmon and sea trout in Sweden which are an important source of economy for local development in history, whereas they have been severely affected by the local hydropower development. At the same time it has also an important tourist river cultural value, especially sport fishing being one of the main reasons for visiting the Nedre Dalälven river. At present the different interests including hydropower production, rural construction, cultural recreation, and ecological restoration and protection intersect together, affecting the landscape of the Nedre Dalälven river. Landscape architecture can coordinate different stakeholder’s interests in a visionary future illustration with ambitions to solve conflicting issues. This thesis analyzed the Nedre Dalälven river space flowing through the Älvkarleby area and the ecological landscape of the shorelines, especially the dilemma caused by the development of hydropower for local wild fish migration and development needs of local recreation activities. This thesis applies the Landscape Character Assessment method to carry out an inventory of the research river riparian landscape as the basis for a proposed ecological restoration and development of a municipal nature reserve divided in three functional zones, through observations, interviews and questionnaires including different stakeholders and interests. Strategy guidelines for ecological function restoration and human recreation needs are given for the three functional zones of the municipal nature reserve. Finally, an in-depth design work-Fish Nature Park, is proposed for the core protection area which is one of the functional zones. The thesis illustrated how landscape design-led research methods can be applied to address fish migration routes and habitat restoration, while also taking into account the needs of local cultural preservation and outdoor recreation. The thesis concludes that the task of applying environmental legislation to hydropower activity in rivers needs to include municipal comprehensive work and issues of additional protections and developments in order to be able to choose the best design solution and find the financing for that.